2018
DOI: 10.1002/ecs2.2372
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preference of an herbivore shapes the habitat distribution of its host plant

Abstract: Plant distributions can be limited by habitat-biased herbivory, but the proximate causes of such biases are rarely known. Distinguishing plant-centric from herbivore-centric mechanisms driving differential herbivory between habitats is difficult without experimental manipulation of both plants and herbivores. Here we tested alternative hypotheses driving habitat-biased herbivory in bittercress (Cardamine cordifolia), which is more abundant under shade of shrubs and trees (shade) than in nearby meadows (sun) wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Previous studies on the plastomes of various parasitic plants indicated strong contraction in the plastomes of parasitic plants (Feng et al., 2016). Gene family contraction has also been found to be one of the major events of nuclear genome evolution of parasitic plants (Alexandre et al., 2018; Cai et al., 2021; Ohigashi et al., 2019; Sun et al., 2018). We found strong signals of gene family contraction in the orchids: Approximately 75% of the conserved gene families in almost all orchids showed contraction and G. elata exhibited the largest extent of gene family contraction (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the plastomes of various parasitic plants indicated strong contraction in the plastomes of parasitic plants (Feng et al., 2016). Gene family contraction has also been found to be one of the major events of nuclear genome evolution of parasitic plants (Alexandre et al., 2018; Cai et al., 2021; Ohigashi et al., 2019; Sun et al., 2018). We found strong signals of gene family contraction in the orchids: Approximately 75% of the conserved gene families in almost all orchids showed contraction and G. elata exhibited the largest extent of gene family contraction (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our developed model should confirm its predictive potential also when applied to seminatural conditions like greenhouse experiments (see Jagiełło et al 2019). Some studies suggest that leaf-miners and leaf-gallers prefer sun-exposed leaves over those growing in the shade (Dai et al 2013;Alexandre et al 2018), but Horváth and Benedek (2009) pointed out that the preference of C. ohridella for shaded vs sun-exposed leaves likely results from seasonal r slope and a intercept of regression, R correlation coefficient, E and SE error and standard error of estimation, n number of corresponding observations. Values of equation parameters are calculated for days, and accumulated degree-days (sum of effective temperatures, SET), K upper asymptote of equation (maximal value of relative mine surface), and corresponding parameter in Verhulst equation assumed as K = 1 variation of leaf microclimate and/or nutritional value of the leaf tissue.…”
Section: Discussionmentioning
confidence: 72%
“…Some studies suggest that leaf-miners and leaf-gallers prefer sun-exposed leaves over those growing in the shade (Dai et al 2013 ; Alexandre et al 2018 ), but Horváth and Benedek ( 2009 ) pointed out that the preference of C. ohridella for shaded vs sun-exposed leaves likely results from seasonal variation of leaf microclimate and/or nutritional value of the leaf tissue. The role of microclimate variability on insect development was analysed by Rebaudo et al ( 2016 ), who concluded ‘…that the model implemented with microclimatic data best predicted observed pest abundances for [their] study sites, but was less accurate than the global dataset model when performed at larger scales’.…”
Section: Discussionmentioning
confidence: 99%
“…However, the statistical signature of these treatment effects was not clear enough to confidently conclude that our field trials substantially altered natural patterns of herbivory by this specialist, given the high degree of stochastic or unexplained variation in herbivore damage we observed across plant patches ( figure S9, table S5). Discovering the biotic and abiotic factors structuring herbivory patterns in natural host populations thus remains a challenge in this system (48) as well as many others (46), and we have not attempted to solve this problem in the present study.…”
Section: Herbivore-inducible Plant Defenses Can Amplify Phytopathogensmentioning
confidence: 98%